MENUJU PERGURUAN TINGGI RESPONSIF GENDER: MENGUKUR KESIAPAN IAIN PONOROGO DALAM IMPLEMENTASI INDIKATOR PTRG MELALUI SWOT ANALYSIS - Yuliani, Irma; Ulfah, Isnatin (Center of Gender Studies and Child of State Islamic Institute of Metro, 2022)
The implementation of gender responsive indicators in higher education is still the homework for almost all campuses in Indonesia, including IAIN Ponorogo. In order toward a gender-responsive institution, there need to be stages that must be carried out by the campus. Through SWOT analysis, this article explains the readiness of IAIN Ponorogo to implement the gender responsive indicators in higher education. The four gender responsive indicators analyzed are the gender mainstreaming institution, gender-responsive in education, research and services, gender-responsive governance and budgeting, and a culture of zero tolerance towards men and women. This study utilized primary data in the form of interviews as well as secondary data in the form of gender responsive indicator in higher education, journal articles, regulations, and other relevant sources. This research shows that basically IAIN Ponorogo already has sufficient capital to realize itself as a gender-responsive higher education. If these capitals could not be managed properly by stakeholders, this research found potential obstacles to the realization of IAIN Ponorogo as a gender responsive higher education. Some important opportunities that are not owned by other tertiary institutions but are owned by IAIN Ponorogo are having a female chancellor with a good gender perspective. This condition indicates a sizable opportunity for IAIN Ponorogo to realize itself as a gender-responsive higher education. Keywords: Gender Mainstreaming, Gender Responsive Higher Education, SWOT Analysis. Abstrak Implementasi indikator perguruan tinggi responsif gender (PTRG) masih menjadi pekerjaan rumah hampir seluruh kampus di Indonesia, tak terkecuali IAIN Ponorogo. Untuk menuju perguruan tinggi responsif gender perlu ada tahapan-tahapan yang harus dilakukan oleh kampus. Melalui analisis SWOT artikel ini menjelaskan kesiapan IAIN Ponorogo dalam mengimplementasikan indikator PTRG. Empat indikator PTRG yang dianalisis adalah kelembagaan PSGA, tridarma perguruan tinggi responsif gender, tata kelola dan penganggaran responsif gender, serta budaya nir-kekerasan terhadap laki-laki dan perempuan. Penelitian ini memanfaatkan data primer berupa wawancara dan juga data sekunder berupa dokumen indikator PTRG, artikel jurnal, regulasi, dan juga sumber-sumber lain yang relevan. Penelitian ini menunjukkan bahwa pada dasarnya IAIN Ponorogo telah memiliki modal yang memadai untuk mewujudkan diri menjadi perguruan tinggi responsif gender. Jika modal-modal tersebut tidak dapat diramu dengan baik oleh para pemangku kepentingan, penelitian ini menemukan potensi yang menghambat mewujudnya IAIN Ponorogo sebagai perguruan tinggi responsif gender. Beberapa peluang penting yang tidak dimiliki oleh Perguruan Tinggi lain namun dimiliki oleh IAIN Ponorogo adalah, memiliki rektor perempuan dengan perspektif gender yang baik. Kondisi ini menunjukkan peluang yang cukup besar bagi IAIN Ponorogo untuk mewujudkan diri menjadi perguruan tinggi responsif gender. Kata Kunci : Pengarusutamaan Gender, Perguruan Tinggi Responsif Gender, Analisis SWOT